Liver Imaging and Data System (LI-RADS) Version 2018 and Other Imaging Features in Intrahepatic Cholangiocarcinoma in Chinese Adults with vs. without Chronic Hepatitis B Viral Infection - Liang, Ying-ying (Can J Gastroenterol Hepatol, 2021)
PURPOSE: To describe liver imaging reporting and data system (LI-RADS) version 2018 and other MRI imaging features in intrahepatic mass-forming cholangiocarcinoma (iCCA) in Chinese adults with vs. without chronic hepatitis B viral (HBV) infection. METHODS: We retrospectively enrolled 89 patients with pathologically proven iCCA after multiphase imaging performed between 2004 and 2017 at a tertiary medical center in southern China. Based on whether patients had chronic HBV, iCCA was divided into two subgroups: HBV-positive (n = 50 patients, including 9 with cirrhosis) vs. HBV-negative (n = 39 patients, including 14 with hepatolithiasis and 25 with no identifiable risk factor for iCCA; none had cirrhosis). Two independent abdominal radiologists in consensus reviewed the largest mass in each patient to assign LI-RADS v2018 features; they also scored each observation's shape and location. Imaging features were compared using chi-square or Fisher's exact tests. RESULTS: Most iCCAs in HBV-positive (88% (44/50)) and HBV-negative (97% (38/39)) patients had at least one LR-M feature. Compared to iCCAs in HBV-negative patients, iCCAs in HBV-positive patients were more likely to have at least one major feature of HCC (46% (23/50) vs. 8% (3/39), P < 0.001) and more likely to be smooth (42% (21/50) vs. 10% (4/39), P = 0.001). Six of 50 (12%) iCCAs in HBV-positive patients and 1/39 (3%) iCCAs in HBV-negative patients had at least one major feature of HCC without any LR-M feature. CONCLUSIONS: In this retrospective single-center study in Chinese adults, iCCAs in HBV-positive patients were more likely to resemble HCCs than iCCAs in HBV-negative patients.